2012
DOI: 10.4049/jimmunol.1101895
|View full text |Cite
|
Sign up to set email alerts
|

Airway Epithelial Expression of TLR5 Is Downregulated in Healthy Smokers and Smokers with Chronic Obstructive Pulmonary Disease

Abstract: The toll-like receptors (TLRs) are important components of the respiratory epithelium host innate defense, enabling the airway surface to recognize and respond to a variety of insults in inhaled air. Based on the knowledge that smokers are more susceptible to pulmonary infection and that the airway epithelium of smokers with chronic obstructive pulmonary disease (COPD) is characterized by bacterial colonization and acute exacerbation of airway infections, we assessed whether smoking alters expression of TLRs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 61 publications
(77 reference statements)
4
39
0
1
Order By: Relevance
“…These observations suggest that smoking-induced changes in the airway epithelium occur early during the pathogenesis of COPD and before decline in lung functon. Surprisingly, however, in contrast to the well-established role of inflammation in progression of alreadyestablished COPD (14,25,26,31,32), genome-wide studies revealed that the overall expression of genes related to inflammation and immunity are downregulated in both the large and small airway epithelia of smokers (19,27,28,33). These observations suggest that the early events in the pathogenesis of COPD in smokers may involve noninflammatory mechanisms.…”
Section: Transatlantic Airway Conferencementioning
confidence: 81%
“…These observations suggest that smoking-induced changes in the airway epithelium occur early during the pathogenesis of COPD and before decline in lung functon. Surprisingly, however, in contrast to the well-established role of inflammation in progression of alreadyestablished COPD (14,25,26,31,32), genome-wide studies revealed that the overall expression of genes related to inflammation and immunity are downregulated in both the large and small airway epithelia of smokers (19,27,28,33). These observations suggest that the early events in the pathogenesis of COPD in smokers may involve noninflammatory mechanisms.…”
Section: Transatlantic Airway Conferencementioning
confidence: 81%
“…Moreover, Wang with his team [66] demonstrated the toll-like receptor(TLR)5, expressed mainly on the apical side of the epithelium, was down-regulated in healthy smokers and smokers with COPD, compared to nonsmokers. The toll-like receptors are important components of the respiratory epithelium host innate defense and TLR-deficient mice develop exhibit impaired CD4 + T cell response to a flagellated pathogen [67], suggesting suppression of airway epithelial TLR5 may contribute to the increased susceptibility of smokers and smokers with COPD to airway flagellated bacterial infection.…”
Section: Inflammation and Immune Changesmentioning
confidence: 99%
“…The activated MUC5AC-core gene expression in smokers may lead to mucus hypersecretion. Down regulation of TLR5 and physiological apical junctional complex(AJC) gene in healthy smokers may be involved in smoking-related susceptibility to airway infection [66, 87]. Overexpression of ubiquitin carboxyl-terminal hydrolase L1 (UCHL1) which is used as a marker of lung cancer in chronic smokers may represent an early event in the complex transformation from normal epithelium to overt malignancy [88].…”
Section: Genetic Alterationsmentioning
confidence: 99%
“…In immunohistochemical staining for human airways using anti-TLR7 antibody, far fewer TLR7-immunopositive cells were observed in both SMG and AEP in subjects with COPD as compared to those without COPD AUC 120-600s from baseline 340/380 ratio (n = 10 for each experiment). It was also reported that TLR5 expression in AEP is significantly reduced in healthy smokers and smokers with COPD compared to that in healthy non-smokers (Wang et al, 2012). Ten reliable intracellular calcium assays were from more than 15 different swine airways.…”
Section: The Expression Of Tlr7 Is Downregulated In Both Airway Smg Amentioning
confidence: 99%